Factor Analysis on Rice Product Labels as a Consideration for Consumer's Purchase Decision In Yogyakarta - Melani Yulinar Khasanah; Jamhari Jamhari; Dwidjono Hadi Darwanto (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2021)
Rice is one of the staple foods consumed by most Indonesians causes rice products to grow in line with consumer demand. As a widely consumed product, rice production labeling is a concern following the latest health issues. Labels are expected to provide useful information in determining products to be purchased by consumers, so it is necessary to know the information that consumers expect. This study aims to determine the attributes on the label that consumers consider when making purchasing decisions. The online questionnaire was filled in by 125 random respondents in Yogyakarta City and Sleman Regency, considering the current conditions (the Covid-19 pandemic). Determination of the factors taken into consideration using the Confirmatory Factor Analyze (CFA) method and appropriate statistical tools were used to analyze the data. The results showed that 74% of the respondents purchased labeled rice products in the last month. As many as 98.65% of respondents who bought labeled rice read the labels before making a purchase decision, and 78.38% considered labeling rice products important. Two factors are considered when making a purchasing decision: product specifications (price and production code) and product quality (organic labeling, net weight, nutritional content, BPOM registration number, and SNI label).